UJI COBA NUKLIR OLEH PRANCIS DI ATMOSFER WILAYAH PASIFIK SELATAN: NUCLEAR TESTING CONDUCTED BY FRANCE OVER THE ATMOSPHERE OF THE SOUTH PACIFIC REGION - Septianingsih, Alizanoor; Izni, Rifdah; Sujatmoko, Andrey (Fakultas Hukum Universitas Trisakti, 2024)
France was one of the countries that developed nuclear power as a source in 1970, and it was for this reason that France in 1973 proposed to conduct nuclear tests in the atmospheric region of the South Pacific. Later, the nuclear tests turned out to be risky, causing losses to countries in the Pacific and Oceania regions, especially Australia and New Zealand. The problems that will be researched are: what are the efforts made by Australia and New Zealand to prevent France from conducting nuclear tests in the South Pacific? The method used in this research is normative juridical, descriptive analytical, using secondary data, which includes primary and secondary legal materials obtained through literature studies, and data analysis is carried out qualitatively, and deductive conclusions are drawn. The conclusion obtained shows that the effort made by Australia, with the intervention of New Zealand, is to file a case against the French action to the International Court of Justice (ICJ) to prevent France from conducting nuclear tests in the atmosphere of the South Pacific region, considering that nuclear testing is one of the things that is prohibited in offshore areas and also in the atmosphere.